Gender, ethnicity and smoking affect pain and function in patients with rotator cuff tears. Issue 9 (12th July 2017) - Maher, Anthony; Leigh, Warren; Brick, Matt; Young, Simon; Millar, James; Walker, Cameron; Caughey, Michael
Abstract : Background: This study is a collation of baseline demographic characteristics of those presenting for rotator cuff repair in New Zealand, and exploration of associations with preoperative function and pain. Data were obtained from the New Zealand Rotator Cuff Registry; a multicentre, nationwide prospective cohort of rotator cuff repairs undertaken from 1 March 2009 until 31 December 2010. Methods: A total of 1383 patients were included in the study. This required complete demographic information, preoperative Flex‐SF (functional score) and pain scores. Following univariate analysis, a multivariate model was used. Results: The average age was 58 years (69% males and 11% smokers). New Zealand Europeans made up 90% and Maori 5%. The average preoperative Flex‐SF was significantly lower (poorer function) in those over 65 years, females, smokers and Maori, in the non‐dominant patients, using a multivariate model. Average preoperative pain scores were significantly worse (higher scores) in females, Maori, Polynesians, smokers, using a multivariate model. Conclusion: This is the largest reported prospective cohort of patients presenting for rotator cuff surgery. Results can be used to understand the effect of rotator cuff tears on the different patients, for example Maori patients who are under‐represented, present younger, with more pain and poorer function.